Handbook for communicating the Philippine centennial of 1998. (National Centennial Commission, 1996)
A handbook that aims to help the communicator present history accurately, to use the 1998 Centennial of the Philippines to unify and harmonize the Filipinos' diverse cultural groupings and to encourage use of keywords and values to increase the public's recall and understanding of the National Centennial Commission's objectives.